Asthma Allergy Immunol 2019
DOI: 10.21911/aai.502
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Bronchiectasis in Adult Patients with Common Variable Immunodeficiency

Abstract: Objective: Common Variable Immunodeficiency (CVID) is a heterogeneous immune disorder characterized by frequent and recurrent upper and lower respiratory tract infections. Although immunoglobulin (Ig) replacement therapy (IgRT) reduces the frequency of infections, complications due to infections of the respiratory tract, particularly bronchiectasis, is still challenging and occur in approximately 20% of patients. Therefore, we aimed to identify independent predictors of bronchiectasis in adult patients with CV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…Also, thrombocytopenia may be due to splenic sequestration or autoimmunity in addition to immune dysregulation. Our group reported that low platelet count is a risk factor for bronchiectasis in patients with CVID [34]. In our study, platelet values were found to be lower in the group with proteinuria, although not statistically significant.…”
Section: Discussioncontrasting
confidence: 56%
“…Also, thrombocytopenia may be due to splenic sequestration or autoimmunity in addition to immune dysregulation. Our group reported that low platelet count is a risk factor for bronchiectasis in patients with CVID [34]. In our study, platelet values were found to be lower in the group with proteinuria, although not statistically significant.…”
Section: Discussioncontrasting
confidence: 56%
“…In the USIDNET (The United States Immunodeficiency Network) registry system, patients with autoimmune cytopenias have been determined to be associated with non-infectious complications, including lymphoproliferation and granulomatous disorders enteropathy, lymphoma, and interstitial pulmonary diseases (16). In another study, reduced platelet count and switched memory B cell ratio was reported to be a risk factor for bronchiectasis (17). Fisher et al (18) reported that autoimmune conditions negatively affect the overall survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of ALP are usually reduced to a normal range by Bone mineral loss is a well-defined complication in chronic lung diseases (26). Bronchiectasis and chronic lung disease may develop due to the frequent respiratory infections in patients with CVID, and lung function loss may occur due to granulomatous lung disease and interstitial lung involvement (27). In addition, patients who develop chronic lung disease use a higher dose of immunosuppressants to control their respiratory complaints and are immobilized, which may lead to bone mineral loss (26,28).…”
Section: Discussionmentioning
confidence: 99%